A slant-angle half-ring magnetic core and a sintering process thereof

CN122599250APending Publication Date: 2026-08-18CHANGXING BOCHENG ELECTRONICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610885109.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-08-18

AI Technical Summary

Technical Problem

针对现有技术的不足,本发明目的在于提供一种带斜角半环形磁芯,以解决现有半环形磁芯烧结变形大、连接桥去除工序繁琐、端面精度低以及高频损耗高的技术问题

Benefits of technology

首先,通过硅热反应自致密化与界面区玻璃隔离的协同作用,能够实现连接桥在不同烧结阶段的调控。其中,硅热反应的局部放热使连接桥提前致密化,其高温抗变形能力优于同质连接桥,烧结后端面对变形量可控制在0.08-0.11mm,相比无连接桥方案降低90%以上;同时界面区玻璃在烧结初期切断连接桥与主体的化学结合,配合降温过程产生的网状微裂纹,使连接桥可在常规端面研磨工序中被一次性磨除,无需独立切割工序,避免了切割带来的微裂纹与二次变形,研磨后端面平面度可达12-16μm。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122599250A_ABST
    Figure CN122599250A_ABST
Patent Text Reader

Abstract

The application discloses a half-ring magnetic core with an inclined angle and a sintering process thereof. The magnetic core in a green body state comprises a half-ring magnetic core body, a connecting bridge at an opening and an interface region between the two; the connecting bridge region is filled with a mixture of Mg powder and SiO2 powder and added with B2O3 sintering aids, and the interface region is filled with a bismuthate low-melting point glass powder with a melting point of 550-650 DEG C. During preparation, sectional atmosphere sintering is adopted, the connecting bridge is densified in advance through silicon thermal reaction to inhibit sintering deformation, meanwhile, the interface glass is used to isolate and reduce thermal stress to weaken the connecting bridge, and the connecting bridge can be removed at one time in an end face grinding process; the application solves the problems of large sintering deformation of the half-ring magnetic core, difficulty in removing the connecting bridge and high high-frequency loss, significantly improves the end face precision, high-frequency performance and splicing consistency of the magnetic core, and is suitable for industrialized production in the fields of 5G communication, new energy vehicles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetic core manufacturing technology, specifically to a beveled semi-annular magnetic core and its sintering process. Background Technology

[0002] As the core magnetic conductor in electronic components such as high-frequency transformers, common-mode chokes, and inductors, the performance of magnetic cores directly affects power conversion efficiency and signal transmission quality. In the manufacturing process of large-size toroidal magnetic cores (typically with an outer diameter greater than 50mm), the integral molding process suffers from problems such as uneven density distribution, easy cracking during demolding, and significant sintering deformation. Furthermore, complete toroidal magnetic cores require specialized winding equipment, making them unsuitable for multi-variety, small-batch production. To address these issues, the industry commonly employs a method of splicing two semi-toroidal magnetic cores into a complete ring. The two semi-rings can be wound separately and then assembled, significantly reducing winding difficulty and process costs. However, existing semi-toroidal magnetic cores and their manufacturing processes still have the following technical problems: Due to the lack of circumferential constraint, the open end of a semi-annular magnetic core is prone to opening or contraction deformation during sintering, leading to a decrease in the flatness of the end face and the formation of uneven air gaps after splicing. This, in turn, causes increased inductance deviation and poor magnetic circuit closure. To solve this problem, Chinese patent CN110788322B discloses a method to prevent core shrinkage deformation during sintering. This method involves pressing an arc-shaped hoop with the core material and then fixing it with a mold to prevent sintering deformation. However, this method requires an additional mold fixing device, increasing process complexity and equipment cost, and is not suitable for continuous production.

[0003] In summary, the existing technology has not yet provided a semi-toroidal core solution that can simultaneously achieve effective suppression of sintering deformation and damage-free removal of bridging. Summary of the Invention

[0004] (a) Technical problems to be solved To address the shortcomings of existing technologies, the present invention aims to provide a semi-annular magnetic core with an angled bevel, thereby solving the technical problems of large sintering deformation, cumbersome process for removing connecting bridges, low end-face precision, and high high-frequency loss in existing semi-annular magnetic cores.

[0005] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: A semi-annular magnetic core with an angled bevel comprises a core body, a connecting bridge, and an interface region in its green state. The core body has a semi-annular structure, with its annular opening connected by the connecting bridge. The interface region is located between the connecting bridge and the core body.

[0006] The connecting bridge region is filled with a mixture of Mg2Si powder and SiO2 powder in a molar ratio of 1:2, and 0.5-1.0 wt% B2O3 sintering aid is added. Mg2Si and SiO2 undergo a silicothermic reaction at high temperature: Mg2Si + 2SiO2 → 2MgO + 3Si. This reaction is exothermic, which can cause a sudden increase in the local temperature of the connecting bridge, completing densification in advance, thereby providing strong anti-deformation support for the semi-annular opening during the subsequent high-temperature sintering stage.

[0007] The interface region is filled with Bi2O3-B2O3-ZnO series low-melting-point glass powder with a melting point of 550-650℃. This glass melts during sintering and is squeezed out of the interface region under the combined action of the volume expansion stress generated by the initial reaction of the connecting bridge and the contraction stress of the magnetic core body. This severs the chemical bond between the connecting bridge and the magnetic core body, leaving only a weak mechanical locking force between them.

[0008] Furthermore, the thickness of the connecting bridge is the same as the thickness of the magnetic core body, and the width of the connecting bridge is 1 / 20 to 1 / 30 of the diameter of the magnetic core body. The thickness of the interface region is 15-25 μm. The average particle size of the Mg2Si powder and SiO2 powder is 50-100 nm to ensure reactivity and mixing uniformity. At least one free end face of the magnetic core body has a 45° chamfer on its upper and lower edges, with a chamfer length of 0.2-0.5 mm, to eliminate stress concentration at the edges, prevent chipping at the end face edges, and provide a visual alignment reference when splicing two semi-rings.

[0009] The fabrication process of the above-mentioned angled semi-annular magnetic core includes the following steps: S1. Green body forming: Ferrite powder, low-melting-point glass slurry, and Mg2Si-SiO2 mixed powder are sequentially filled into the partitioned mold. The mold is pressed into shape in one step under a pressure of 200-250MPa, with a holding time of 1-3s. After demolding, a semi-annular green body with connecting bridges is obtained. The low-melting-point glass slurry is prepared by mixing low-melting-point glass powder and anhydrous ethanol at a mass ratio of 1:1.5-2.5. After coating, the ethanol is allowed to completely evaporate to form a dry film interface layer.

[0010] S2. Segmented Atmosphere Sintering: The green blank is placed in a sintering furnace and sintered using segmented atmosphere and segmented temperature control. Specifically, this includes the following sub-steps: S21. Debinding stage: In an air atmosphere, heat to 600℃ at a heating rate of 2-3℃ / min and hold for 25-35min to remove the organic binder in the green body and prevent the rapid volatilization of the binder from causing cracking of the green body.

[0011] S22, Interface Activation and Pre-Modification Stage: Switch to a nitrogen atmosphere, control the oxygen content in the furnace to ≤50ppm, heat to 800-900℃, and hold for 10-20 minutes. Within this temperature range, the low-melting-point glass completely melts into a low-viscosity liquid phase; simultaneously, the Mg2Si-SiO2 mixture within the connecting bridge begins to undergo a preliminary reaction. The resulting volume expansion stress, combined with the contraction stress of the magnetic core body, forces the molten glass out of the interface region, severing the chemical bond between the connecting bridge and the core body. Furthermore, the boron in the glass... 3+ Zn 2+ It begins to diffuse towards the end face of the magnetic core and the grain boundaries.

[0012] S23. Silicothermic Reaction and Self-Denseization Stage: Maintain a nitrogen atmosphere and raise the temperature to 900-1050℃, holding for 5-10 minutes. A silicothermic reaction occurs within the connecting bridge: Mg2Si + 2SiO2 → 2MgO + 3Si. This reaction is strongly exothermic, releasing heat that causes the local instantaneous temperature in the connecting bridge area to reach 1250-1400℃, exceeding the furnace set temperature. This localized high temperature promotes rapid densification of the connecting bridge, allowing it to maintain its intact structure during the subsequent high-temperature sintering stage, thus effectively resisting the shrinkage deformation of the semi-annular open end. Simultaneously, the MgO generated in the reaction... 2+ It begins to diffuse towards the grain boundaries of the magnetic core.

[0013] S24. High-temperature sintering and synergistic modification stage: Maintain a nitrogen atmosphere, raise the temperature to 1320-1380℃, and hold for 2.5-3.5 hours. The core body is fully densified during this stage. Mg from the connecting bridge... 2+ With B from the interface area 3+ Zn 2+ Simultaneous segregation at grain boundaries forms a Mg-B-Zn composite high-resistivity grain boundary phase, which can block eddy current paths and significantly reduce high-frequency eddy current losses. Simultaneously, at the splicing end face of the magnetic core, due to the gradient distribution of diffused ion concentration, a gradient composite insulating layer with a thickness of 50-100 μm is formed in situ. The resistivity of this insulating layer is higher than that inside the magnetic core, which can further suppress edge eddy current losses at the splicing air gap and fill minor defects on the end face, improving the splicing fit.

[0014] S25. Cooling and Self-Weakening Stage: Cool to room temperature at a rate of 2-3℃ / min. This is because the reaction product MgO within the connecting bridge has a thermal expansion coefficient of approximately 13.5 × 10⁻⁶. -6 / K), Si (thermal expansion coefficient approximately 2.6 × 10⁻⁶) -6 The coefficients of thermal expansion of the K phase and the residual glass phase, as well as between them and the connecting bridge matrix, are significantly different. During the cooling process, a network of thermal stress microcracks are generated inside the connecting bridge, which greatly reduces the mechanical strength of the connecting bridge to less than 15% of its densified strength, making it very easy to remove in the subsequent grinding process.

[0015] S3. Through-type grinding: A double-end through-type grinding machine is used, with a 600-800 grit grinding wheel, a grinding wheel speed of 1200-1800 rpm, and a feed speed of 3-7 mm / s. The two end faces of the sintered magnetic core are ground simultaneously to remove the severely weakened connecting bridge in one go, and two flat, free end faces without micro-cracks are obtained.

[0016] S4. Cleaning and drying: Place the ground magnetic core in an ultrasonic cleaning tank and clean it with deionized water to remove grinding dust; then dry it with hot air to obtain the finished product.

[0017] In the above technical solution, the molar ratio of Mg2Si powder to SiO2 powder is 1:2, which is the stoichiometric ratio for the silicothermic reaction, ensuring complete reaction. The amount of B2O3 sintering aid added is 0.5-1.0 wt%. Below 0.5 wt%, the densification effect on the connecting bridge is insufficient; above 1.0 wt%, excessive liquid phase is generated, leading to a decrease in the high-temperature strength of the connecting bridge. The melting point range of the low-melting-point glass in the interface region (550-650℃) ensures complete melting in the S22 stage while preventing premature softening during the binder removal stage. The oxygen content in the nitrogen atmosphere is controlled below 50 ppm to prevent oxidation of Mg2Si and the reaction product Si, ensuring the normal progress of the silicothermic reaction.

[0018] This invention, through the synergistic design of connecting bridge materials, interface materials, and sintering processes, enables the connecting bridge to simultaneously play a triple role during sintering: a high-temperature support, a self-weakening fracture body, and a grain boundary modified ion source. Ultimately, it is removed in one step during the conventional end-face grinding process, while simultaneously forming a high-resistance gradient insulation layer in situ on the end face of the magnetic core. This significantly improves the end-face accuracy, high-frequency performance, and splicing consistency of the semi-toroidal magnetic core.

[0019] (III) Beneficial Effects Compared with the prior art, the present invention has the following beneficial effects: Firstly, the synergistic effect of self-densification by the silicon thermal reaction and the glass isolation in the interface region enables the control of the connecting bridge at different sintering stages. Specifically, the localized exothermic reaction of the silicon thermal reaction densifies the connecting bridge in advance, resulting in superior high-temperature deformation resistance compared to homogeneous connecting bridges. The deformation of the sintered end face can be controlled within 0.08-0.11 mm, a reduction of over 90% compared to solutions without connecting bridges. Simultaneously, the glass in the interface region severs the chemical bond between the connecting bridge and the substrate in the early stages of sintering. Combined with the network of microcracks generated during the cooling process, the connecting bridge can be removed in a single pass during conventional end-face grinding, eliminating the need for a separate cutting process. This avoids microcracks and secondary deformation caused by cutting, achieving a surface flatness of 12-16 μm at the ground end face.

[0020] Secondly, it simplifies the manufacturing process by applying the silicon thermal reaction to the design of the semi-toroidal magnetic core connecting bridge, enabling the connecting bridge to simultaneously perform multiple functions such as high-temperature structural support, self-weakening fracture, and grain boundary modification ion source. It eliminates the need for pre-doping grain boundary modifiers into the main powder, saving the doping and mixing process, reducing process complexity and quality control difficulty, and avoiding the permeability loss that may result from overall doping.

[0021] Finally, during the sintering process, this invention generates a composite insulating layer of controllable thickness in situ at the splicing end face. This layer has a resistivity higher than that inside the magnetic core, which can block the edge eddy current path at the splicing air gap, further reducing eddy current losses. The glass-rich phase on the end face surface can fill tiny defects, increasing the effective contact area of ​​the end face and controlling the inductance deviation after splicing within ±2%. At the same time, it improves the mechanical strength of the end face, reducing edge chipping and corner breakage during handling and splicing. This gradient layer is metallurgically bonded to the substrate, with good adhesion, requiring no additional coating process. Attached Figure Description

[0022] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings: Figure 1 This is a schematic diagram of the green state of a semi-annular magnetic core with an angled bevel, according to this application.

[0023] Figure 2 This is a schematic diagram of a finished product of a beveled semi-annular magnetic core according to this application.

[0024] Figure 3 This is a schematic diagram of the finished product of Embodiment 1 of the beveled semi-annular magnetic core of this application.

[0025] Figure 4 This is a schematic diagram of the finished product of Embodiment 2 of a beveled semi-annular magnetic core of this application.

[0026] Figure 5 This is a schematic diagram of the finished product of Embodiment 3 of a beveled semi-annular magnetic core according to this application.

[0027] Figure 6 This is a schematic diagram of the finished product of Comparative Example 1 of a semi-annular magnetic core with an angled bevel, according to this application.

[0028] Figure 7 This is a schematic diagram of the finished product of Comparative Example 2 in a semi-annular magnetic core with an angled bevel according to this application.

[0029] Figure 8 This is a schematic diagram of the finished product of Comparative Example 3 in a beveled semi-annular magnetic core of this application.

[0030] Figure 9 This is a schematic diagram of the finished product of Comparative Example 4 in a semi-annular magnetic core with an angled bevel, according to this application.

[0031] Wherein: 1-Magnetic core body, 2-Connecting bridge, 3-Interface area. Detailed Implementation

[0032] The following will refer to the appendix in the examples of this invention. Figures 1-9 The technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] The semi-annular magnetic cores prepared in the various embodiments and comparative examples of this invention have the same nominal dimensions corresponding to a complete annular core: outer diameter 60 mm, inner diameter 30 mm, and thickness 15 mm. The main body of the magnetic core is made of manganese-zinc ferrite powder with an initial magnetic permeability of 2500 and an average particle size of 2 μm. Polyvinyl alcohol (PVA) is added at 1.2 wt% of the total mass of the powder as a molding binder.

[0034] Example 1 This embodiment provides a semi-annular magnetic core with an angled bevel, the material composition and manufacturing process of which are as follows: Magnetic core body 1: The upper and lower edges of the free end face are machined with a 45° chamfer, and the chamfer length is 0.3mm.

[0035] Connecting bridge region: Filled with a powder mixture of Mg2Si powder and SiO2 powder in a molar ratio of 1:2, with an average particle size of 80nm for both powders; 0.8wt% B2O3 is added as a sintering aid. The connecting bridge width is 2.5mm (approximately 1 / 24 of the outer diameter), and the thickness is the same as the core body thickness, 15mm.

[0036] Interface region: Bi2O3-B2O3-ZnO series low melting point glass powder is used, with a mass composition of 65% Bi2O3, 20% B2O3, and 15% ZnO. The melting point is approximately 580℃, and the average particle size is approximately 3μm. The dry film thickness in the interface region is approximately 20μm.

[0037] Its preparation process includes the following steps: S1. Green Blank Forming: A vertical hydraulic forming machine is used. The inner cavity of the mold is pre-divided into a main body area, an interface layer area, and a connecting bridge area, corresponding to the magnetic core body, the interface area, and the connecting bridge, respectively. First, the above-mentioned manganese-zinc ferrite powder is filled into the main body area and the surface is smoothed. Low melting point glass powder and anhydrous ethanol are mixed at a mass ratio of 1:2 to form a uniform slurry, which is then evenly coated on the interface area between the connecting bridge and the magnetic core body. After the ethanol has completely evaporated, a dry film interface layer with a thickness of about 20μm is formed. Mg2Si-SiO2 mixed powder is filled into the connecting bridge area and the surface is smoothed. The mold is formed in one step under a forming pressure of 220MPa, with a holding time of 2s. After demolding, a semi-annular green blank with connecting bridges is obtained.

[0038] S2. Segmented Atmosphere Sintering: Place the above green blanks in a fully automatic bell-shaped furnace and perform segmented atmosphere sintering according to the following procedure: S21 Debinding Stage: Under air atmosphere, heat to 600℃ at a heating rate of 2.5℃ / min and hold for 30 minutes to fully remove the organic binder from the green body.

[0039] S22 Interface Activation and Pre-Modification Stage: Switch to nitrogen atmosphere, control the oxygen content in the furnace to not exceed 30ppm, heat to 850℃ at a heating rate of 1.5℃ / min, and hold for 15min.

[0040] S23 Silicon thermal reaction and self-densification stage: Maintain the above nitrogen atmosphere, heat to 980℃ at a heating rate of 2℃ / min, and hold for 8min.

[0041] S24 High-temperature sintering and synergistic modification stage: Maintain the above nitrogen atmosphere, heat to 1350℃ at a heating rate of 1.5℃ / min, and hold for 3 hours.

[0042] S25 Cooling self-weakening stage: Cool to room temperature at a cooling rate of 2.5℃ / min.

[0043] S3. Through-grinding: A double-end-face through-grinding machine is used, with a 600-mesh grinding wheel, a grinding wheel speed of 1500 rpm, and a feed speed of 5 mm / s. The two end faces of the sintered magnetic core are ground simultaneously until the weakened connecting bridge is completely removed, resulting in two flat free end faces.

[0044] S4. Cleaning and drying: Place the ground magnetic core in an ultrasonic cleaning tank and clean it with deionized water for 5 minutes; then place it in a hot air drying oven and dry it at 80°C for 20 minutes to obtain the finished product.

[0045] Final product image as shown Figure 3 As shown.

[0046] Example 2 The difference between this embodiment and Embodiment 1 is that: The width of the connecting bridge is adjusted to 2.0 mm (approximately 1 / 30 of the outer diameter); the interface activation temperature in step S22 is adjusted to 820℃; and the silicon thermal reaction temperature in step S23 is adjusted to 920℃.

[0047] The remaining material composition, structural parameters and process steps are exactly the same as in Example 1.

[0048] Final product image as shown Figure 4 As shown.

[0049] Example 3 The difference between this embodiment and Embodiment 1 is that the width of the connecting bridge is adjusted to 3.0 mm (approximately 1 / 20 of the outer diameter); the glass in the interface area uses a Bi2O3-B2O3-ZnO system but with a different ratio, and its mass composition is 60% Bi2O3, 25% B2O3, and 15% ZnO, with a melting point of approximately 560°C. In step S22, the interface activation temperature is adjusted to 880℃; In step S23, the temperature of the silicon thermal reaction is adjusted to 1020℃.

[0050] The remaining material composition, structural parameters and process steps are exactly the same as in Example 1.

[0051] Final product image as shown Figure 5 As shown.

[0052] Comparative Example 1 This comparative example is a conventional semi-annular magnetic core without connecting bridges. An open-type semi-annular green blank was directly pressed using a mold. The green blank consisted only of the same manganese-zinc ferrite powder as in Example 1, without connecting bridge or interface regions. The sintering process was as follows: the temperature was increased to 600℃ at 2.5℃ / min and held for 30 minutes in air to remove the binder; then the temperature was increased to 1350℃ at 1.5℃ / min and held for 3 hours; finally, the temperature was decreased to room temperature at 2.5℃ / min. The remaining forming and post-processing steps were the same as in Example 1.

[0053] Final product image as shown Figure 6 As shown, the deformation deviation of its end face reaches 0.87mm.

[0054] Comparative Example 2 This comparative example is a semi-annular magnetic core with homogeneous connecting bridges and no interface region. The core body and connecting bridges were simultaneously pressed using a mold. The entire green blank was composed of the same manganese-zinc ferrite powder as in Example 1. No interface layer was provided between the connecting bridge area and the main body area, and the connecting bridge width was 2.5 mm. The sintering process was the same as in Comparative Example 1. After sintering, the connecting bridges were removed using a diamond cutter, followed by the same grinding, cleaning, and drying processes as in Example 1.

[0055] Final product image as shown Figure 7 As shown, microcracks are clearly visible on its end face.

[0056] Comparative Example 3 This comparative example is a semi-toroidal magnetic core with homogeneous connecting bridges and pre-added grain boundary modifiers. In the same manganese-zinc ferrite powder as Comparative Example 2, 0.1 wt% MgO was pre-added as a grain boundary modifier, and the remaining structural parameters, sintering process, and post-treatment procedures were the same as those in Comparative Example 2.

[0057] Final product image as shown Figure 8 As shown, microcracks are clearly visible on its end face.

[0058] Comparative Example 4 This comparative example uses the same connecting bridge material as Example 1, with a connecting bridge width of 2.5 mm, but without an interface area. That is, the connecting bridge is in direct contact with the magnetic core body, and there is no low-melting-point glass insulating layer. All other material selections, structural parameters, molding pressure, sintering process, and post-processing steps are exactly the same as in Example 1.

[0059] Final product image as shown Figure 9 As shown, a large area of ​​chipped edges is clearly visible on its end face.

[0060] Performance Testing and Result Analysis 1. Performance Testing Methods End face deformation: A high-precision coordinate measuring machine was used to measure the maximum offset of the center of the free end face of the sintered, unpolished magnetic core relative to the design reference plane. Each sample was measured three times, and the arithmetic mean was taken as the test result.

[0061] Flatness after grinding: The flatness of the free end face of the magnetic core after grinding was measured using a contact flatness measuring instrument. Each sample was measured three times, and the arithmetic mean was taken as the test result.

[0062] End face defect observation: Observe the end face and edge area after grinding, and record whether there are defects such as micro-cracks and edge chipping.

[0063] Volume resistivity: The volume resistivity of the magnetic core was measured at room temperature using a four-probe resistivity meter.

[0064] High-frequency eddy current loss: The eddy current loss per unit volume of the magnetic core was measured using a soft magnetic material AC magnetic performance tester under the conditions of room temperature, frequency of 100kHz, and magnetic flux density of 200mT.

[0065] Splicing inductance deviation: Two semi-toroidal cores prepared in the same batch were spliced ​​into a complete ring, and their inductance value was measured using an LCR meter. The maximum deviation of the inductance value of 10 groups of samples from the nominal value was calculated.

[0066] 2. Test Results The performance test results of each embodiment and comparative example are shown in Table 1.

[0067] Table 1. Performance comparison of each embodiment and comparative example. 3. Results Analysis a. Sintering deformation control effect The end-face deformation in Examples 1-3 was controlled within the range of 0.07-0.10 mm, which is approximately 88%-92% lower than the 0.87 mm in Comparative Example 1 without a connecting bridge, and approximately 62%-73% lower than the 0.26 mm in Comparative Example 2 using a homogeneous connecting bridge. These results demonstrate that the present invention achieves pre-densification of the connecting bridge through a silicon thermal reaction, providing stronger high-temperature structural support and effectively suppressing sintering deformation at the open end of the semi-annular magnetic core. In Example 3, due to the wider connecting bridge and higher silicon thermal reaction temperature, densification was more complete, resulting in the smallest deformation of 0.07 mm.

[0068] b. Removal of connecting bridges and end-face quality The connecting bridges in Examples 1-3 can all be removed in a single pass during conventional end-face grinding, without the need for a separate cutting process; the ground end face has no visible microcracks, chipping, or other defects, and the flatness reaches 11-15 μm. Comparative Examples 2 and 3 require an additional cutting process to remove the connecting bridges, the cut surfaces have obvious microcracks, and the flatness of the ground end face is only 28-29 μm.

[0069] Although Comparative Example 4 used the same connecting bridge material as Example 1, the lack of an interface zone resulted in a strong chemical bond between the connecting bridge and the main body during sintering. During grinding, the fracture surface of the connecting bridge extended to the end face of the main body, leading to large-area edge chipping, a flatness of only 35 μm, and severe end-face defects. The above comparison demonstrates that extruding and cutting the low-melting-point glass in the interface zone is crucial for protecting the integrity of the end face and achieving damage-free removal of the connecting bridge.

[0070] c. Magnetic properties and splicing performance The volume resistivity of Examples 1-3 reached 5.9 × 10⁻⁶. 5 -6.4×10 5 The Ω·cm efficiency was improved by approximately 84%-106% compared to Comparative Examples 1 and 2, and by approximately 37%-49% compared to Comparative Example 3 with MgO grain boundary modifier alone; the eddy current loss per unit volume under 100kHz / 200mT conditions was 198-218kW / m. 3Compared to Comparative Examples 1 and 2, the inductance is reduced by approximately 31%-39%, and compared to Comparative Example 3, the inductance is reduced by approximately 19%-27%. Meanwhile, the splicing inductance deviation of the embodiment is controlled within ±2%, significantly better than each comparative example.

[0071] Comparative Example 4 suffered from severe edge chipping at the end face, resulting in poor bonding during splicing and an inductance deviation of ±6.8%. Furthermore, its resistivity and losses were significantly worse than those of the Example 4. This indicates that the absence of the interface region not only affects the integrity of the end face but also hinders the Mg... 2+ B 3+ Zn 2+ Effective diffusion towards the main grain boundaries prevents the formation of high-resistivity grain boundary phases and gradient insulating layers.

[0072] The above results demonstrate that the structural design and sintering method of this invention effectively improve the high-frequency performance and splicing consistency of the magnetic core.

[0073] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A semi-annular magnetic core with an angled bevel, characterized in that, In the green state, it includes a magnetic core body (1), a connecting bridge (2) and an interface region (3). The magnetic core body (1) is a semi-annular structure, and its annular opening is connected by the connecting bridge (2). The interface region (3) is located between the connecting bridge (2) and the magnetic core body (1). The connecting bridge region corresponding to the connecting bridge (2) is filled with a mixture of Mg2Si powder and SiO2 powder in a molar ratio of 1:2, and B2O3 sintering aid accounting for 0.5-1.0 wt% of the total mass of the mixed powder is added. The interface region (3) is filled with low melting point glass powder.

2. The obliquely angled semi-annular magnetic core according to claim 1, characterized in that, The low-melting-point glass powder is a Bi2O3-B2O3-ZnO series glass powder, and the melting point of the low-melting-point glass powder is 550-650℃.

3. The obliquely angled semi-annular magnetic core according to claim 1, characterized in that, The thickness of the connecting bridge (2) is the same as the thickness of the magnetic core body (1), and the width of the connecting bridge (2) is 1 / 20 to 1 / 30 of the diameter of the magnetic core body (1); the thickness of the interface region (3) is 15-25 μm.

4. The obliquely angled semi-annular magnetic core according to claim 1, characterized in that, The upper and lower edges of at least one free end face of the magnetic core body (1) are provided with a 45° chamfer, and the chamfer length is 0.2-0.5mm.

5. A manufacturing process for a beveled semi-annular magnetic core as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Green body forming: Ferrite powder, low melting point glass paste and Mg2Si-SiO2 mixed powder are sequentially filled into the partition mold and pressed into shape to obtain a semi-annular green body with connecting bridges. S2. Segmented atmosphere sintering: The green blank is placed in a sintering furnace and sintered using segmented atmosphere and segmented temperature control. S3. Through-grinding: Grind the two end faces of the sintered magnetic core to remove the weakened connecting bridge; S4. Cleaning and drying: Clean the polished magnetic core and then dry it.

6. The fabrication process of a beveled semi-annular magnetic core according to claim 5, characterized in that, Step S2 includes: S21, Debinding: In an air atmosphere, heat to 600℃ at a heating rate of 2-3℃ / min and hold for 25-35min; S22, Interface Activation: Switch to nitrogen atmosphere, control the oxygen content in the furnace to ≤50ppm, heat to 800-900℃, and hold for 10-20min; S23, Silicothermic reaction: Maintain a nitrogen atmosphere, raise the temperature to 900-1050℃, and hold for 5-10 minutes; S24. High-temperature sintering: Maintain a nitrogen atmosphere, raise the temperature to 1320-1380℃, and hold for 2.5-3.5 hours; S25. Cooling: Cool to room temperature at a rate of 2-3℃ / min.

7. The fabrication process of a semi-annular magnetic core with an angled bevel according to claim 5, characterized in that, In step S1, the pressing pressure is 200-250 MPa, and the holding time is 1-3 seconds.

8. The fabrication process of a semi-annular magnetic core with an angled bevel according to claim 5, characterized in that, In step S1, the low-melting-point glass slurry is prepared by mixing low-melting-point glass powder and anhydrous ethanol at a mass ratio of 1:1.5-2.

5. After coating, the ethanol is allowed to evaporate completely to form a dry film interface layer.

9. The fabrication process of a beveled semi-annular magnetic core according to claim 5, characterized in that, In step S3, the grinding process uses a double-end through-type grinding machine, selects a 600-800 mesh grinding wheel, the grinding wheel speed is 1200-1800 rpm, and the feed speed is 3-7 mm / s.

Citation Information

Patent Citations

  • A method to prevent core sintering deformation during the sintering process

    CN110788322B